Association between the number of endotracheal intubation attempts and rates of adverse events in a paediatric emergency department. Issue 8 (6th December 2021) - Abid, Edir S; Miller, Kelsey A; Monuteaux, Michael C; Nagler, Joshua
Abstract : Background: Challenges in emergent airway management in children can affect intubation success. It is unknown if number of endotracheal intubation attempts is associated with rates of adverse events in the paediatric ED setting. Objective: We sought to (1) Identify rates of intubation-related adverse events, (2) Evaluate the association between the number of intubation attempts and adverse events in a paediatric ED, and (3) Determine the effect of videolaryngoscopy on these associations. Design and methods: We performed a retrospective observational study of patients who underwent endotracheal intubation in a paediatric ED in the USA between January 2004 and December 2018. Data on patient-related, provider-related and procedure-related characteristics were obtained from a quality assurance database and the health record. Our primary outcome was frequency of intubation-related adverse events, categorised as major and minor. The number of intubation attempts was trichotomised to 1, 2, and 3 or greater. Multivariable logistic regression models were used to determine the relationship between the number of intubation attempts and odds of adverse events, adjusting for demographic and clinical factors. Results: During the study period, 628 patients were intubated in the ED. The overall rate of adverse events was 39%. Hypoxia (19%) was the most common major event and mainstem intubation (15%) the most common minor event. 72% patients were successfully intubated on the first attempt. With two intubation attempts, the adjusted odds of any adverse event were 3.26 (95% CI 2.11 to 5.03) and with ≥3 attempts the odds were 4.59 (95% CI 2.23 to 9.46). Odds similarly increased in analyses of both major and minor adverse events. This association was consistent for both traditional and videolaryngoscopy. Conclusion: Increasing number of endotracheal intubation attempts was associated with higher odds of adverse events. Efforts to optimise first attempt success in children undergoing intubation may mitigate this risk and improve clinical outcomes.